The influence of prior knowledge and viewing repertoire on learning from video - de Boer, J.; Kommers, Petrus; de Brock, B.; Tolboom, J. (Springer, 2016)
© 2014, Springer Science+Business Media New York.Video is increasingly used as an instructional tool. It is therefore becoming more important to improve learning of students from video. We investigated whether student learning effects are influenced through an instruction about other viewing behaviours, and whether these learning effects depend on their prior knowledge. In a controlled environment, 115 students watched a number of instructional videos about the technical equipment needed in a course on digital photography. Every second student was instructed about other possible viewing behaviours. A pre-post-retention test was carried out to calculate learning effects. The differences with respect to the learning effects of students who received an awareness instruction on an alternative viewing strategy were not significantly different. The differences as observed in our earlier experiment however could not be reproduced. Students with a broad viewing repertoire showed higher learning effects than students with a narrow repertoire. Furthermore, students with a strategic viewing approach also showed higher learning effects. Certain conditions have to be met: the technical and didactical quality of the video must be good, the integration in a learning task must be apparent, students must be aware of their viewing behaviour, and teachers must be aware of their students’ viewing behaviour in order to enrich the viewing repertoire of students when they have at least some basic knowledge e.g. after several lessons on the topics at hand. In future research, this study should be replicated using more complex video episodes than the instruction videos we used in our experiments that were only on the factual knowledge level of the taxonomy of Bloom. Moreover, replication of this study with a larger sample size could yield a significant improvement in learning effects. This is plausible because students need an amount of prior knowledge beyond a certain threshold value in order to be able to expand their knowledge network in their long term memory. Finally, additional media player functionality, facilitating effective student learning from video, can be described based on the results of this study.